2013
DOI: 10.1002/grl.50373
|View full text |Cite
|
Sign up to set email alerts
|

Secondary planetary waves in the middle and upper atmosphere following the stratospheric sudden warming event of January 2012

Abstract: [1] The role of planetary waves in causing stratospheric sudden warmings (SSWs) is well understood and quantified. However, recent studies have indicated that secondary planetary waves are excited in the mesosphere and lower thermosphere following SSWs. We use a version of the Whole Atmosphere Community Climate Model constrained by reanalysis data below 50 km to simulate the SSW of January 2012, a minor warming followed by the formation of an elevated stratopause. We document the occurrence of enhanced Eliasse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
174
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(200 citation statements)
references
References 33 publications
(62 reference statements)
17
174
1
Order By: Relevance
“…5b suggests the anomalies are approximately phase-locked. The westward propagation of the MLT wave number 1 post-SSW has been seen using SABER temperatures as well as in WACCM-SD simulations of a minor SSW in January 2012 (Chandran et al, 2013). During this latter event, Chandran et al (2013) observed a westward propaga- tion of the MLT wave number 1 starting 1 day prior to the SSW onset, although in the stratosphere between 40-50 km the PW remained quasi-stationary.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…5b suggests the anomalies are approximately phase-locked. The westward propagation of the MLT wave number 1 post-SSW has been seen using SABER temperatures as well as in WACCM-SD simulations of a minor SSW in January 2012 (Chandran et al, 2013). During this latter event, Chandran et al (2013) observed a westward propaga- tion of the MLT wave number 1 starting 1 day prior to the SSW onset, although in the stratosphere between 40-50 km the PW remained quasi-stationary.…”
Section: Discussionmentioning
confidence: 73%
“…The westward propagation of the MLT wave number 1 post-SSW has been seen using SABER temperatures as well as in WACCM-SD simulations of a minor SSW in January 2012 (Chandran et al, 2013). During this latter event, Chandran et al (2013) observed a westward propaga- tion of the MLT wave number 1 starting 1 day prior to the SSW onset, although in the stratosphere between 40-50 km the PW remained quasi-stationary. In this case the behaviour was interpreted as in situ forcing of PWs in the MLT due to instabilities of the background zonal wind field (Chandran et al, 2013).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The "central date" of these major SSWs is the day when the polar jet reverses from eastward to anomalously westward wind at 10 hPa (about 32 km altitude) and 60 • N. A compilation of major SSW central dates is given, for example, by Charlton and Polvani (2007) Table 1 for the time period considered in our study. This compilation is mainly based on the references Cohen and Jones (2011) and Chandran et al (2013). In addition, the type of the major SSW is classified by either "D" for "displacement" or "S" for "split", depending on whether the polar vortex was either displaced by a strong planetary wave number one, or split into two parts by a strong planetary wave number two (see also Charlton and Polvani, 2007).…”
Section: Satellite Observations Of Gravity Wave Amplitudes Momentum mentioning
confidence: 99%
“…However, because the winds only reversed above the 10 hPa level at 60 • N the criterion for a major warming is not matched (see, for example, Chandran et al, 2014), and the SSW in January 2012 is classified only as a minor SSW, even though after the warming a new elevated stratopause is formed in the mesosphere (Chandran et al, 2013). If an average over a wider latitude range of 60-80 • N is considered, like in Fig.…”
Section: Satellite Observations Of Gravity Wave Amplitudes Momentum mentioning
confidence: 99%